Role of the nurses in care for patients with schizophrenia (Research, Society and Development, 2021)
Currently, with the Psychiatric Reform, there are bigger and better devices to work with patients with mental disorders and nursing plays a significant role in the care offered to this user. Schizophrenia is a mental illness that is defined by distortions of thought, perception and affect. Thus, the objective of this work is to report the importance of nursing care for schizophrenic patients, through a descriptive bibliographic study. Inclusion criteria were articles, manuals of the Ministry of Health, monographs, dissertations, theses available in full, published and written in Portuguese, consistent with the research theme and published in the period from 2015 to 2020. The exclusion criteria were : materials that did not address the proposed theme and/or did not meet the inclusion criteria described above and outside the period stipulated for the research. Nursing is essential in these cases because it is this professional who draws nursing diagnoses that elaborate the systematization aiming at risk factors and possible injuries. Through this research it was possible to know about the evolution of psychiatric treatments and a little more about schizophrenic disorders. Above all, this work made it possible to reach a holistic view of the nursing role in caring for these patients, not just with a technical-medicinal focus.